PUC NO LAR: AÇÕES DA PUC MINAS PARA APOIO ÀS INSTITUIÇÕES DE LONGA PERMANÊNCIA PARA IDOSOS DURANTE A PANDEMIA - Silva, Vitória N.; Silva, Thaís C. D.; Vieira, Igor F. N.; Silva, Verônica B.; Almeida, Júlia G. R.; Amaral, Cleia M. G.; Guerra, Henrique Leonardo; Horta, Natália de Cássia; Souza, Marina C. M. R.; Lacerda, Tatiana Teixeira Barral de (Sinapse Múltipla, 2020)